2018
DOI: 10.2903/sp.efsa.2018.en-1432
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of EC/EFSA questionnaire (2016) on use of Whole Genome Sequencing (WGS) for food‐ and waterborne pathogens isolated from animals, food, feed and related environmental samples in EU/EFTA countries

Abstract: Whole Genome Sequencing (WGS) is becoming increasingly used in public health and food safety laboratories. To date, there is a wide variation in the level of implementation of WGS among laboratories from different sectors in different countries, the type of analysis employed and the data interpretation. To gather information on the WGS capacity of food safety/veterinary laboratories in the European Union (EU) and associated countries (EFTA), the European Commission (DG SANTE) and the European Food Safety Autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…We employed the pathogen N. meningitidis as a proof-of-concept by designing a bioinformatics workflow (Figure 1) that incorporates different quality checks (Table 1) and relevant typing schemas (Table 2) with the aim of either extracting information that ensures backward compatibility with currently existing “classical” molecular biology techniques (e.g., serotyping), or alternatively taking advantage of the full potential offered by WGS by extracting information at the scale of the full genome (e.g., cgMLST). Our study is relevant because recent surveys by both the EFSA (García Fierro et al, 2018) and the ECDC (Revez et al, 2017) have indicated that, at least in Europe, the data analysis and required expertise remain substantial bottlenecks impeding the implementation of NGS for routine use in microbiology. For NRCs and NRLs, as well as other laboratories working under a quality system, a harmonized framework for validation of the WGS workflow presents an additional obstacle (Rossen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed the pathogen N. meningitidis as a proof-of-concept by designing a bioinformatics workflow (Figure 1) that incorporates different quality checks (Table 1) and relevant typing schemas (Table 2) with the aim of either extracting information that ensures backward compatibility with currently existing “classical” molecular biology techniques (e.g., serotyping), or alternatively taking advantage of the full potential offered by WGS by extracting information at the scale of the full genome (e.g., cgMLST). Our study is relevant because recent surveys by both the EFSA (García Fierro et al, 2018) and the ECDC (Revez et al, 2017) have indicated that, at least in Europe, the data analysis and required expertise remain substantial bottlenecks impeding the implementation of NGS for routine use in microbiology. For NRCs and NRLs, as well as other laboratories working under a quality system, a harmonized framework for validation of the WGS workflow presents an additional obstacle (Rossen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A gap nevertheless still exists between the acclaimed success and the everyday implementation and usage of this technology in a public health setting, especially for many national reference laboratories (NRLs) and centers (NRCs) in smaller and/or less developed countries, which do not always have access to the same resources that are available for public health agencies in larger and/or more developed countries that already routinely process large volumes of samples with NGS technologies (WHO, 2018). In Europe, recent surveys in 2016 by both the European Food Safety Authority (EFSA) (García Fierro et al, 2018) and the European Centre for Disease Prevention and Control (ECDC) (Revez et al, 2017) indicated that NGS was being used in 17 out of 30 and 25 out 29 responding constituents, respectively, and that large discrepancies existed between different European countries in the advancement of implementing this technology for different microbial pathogens of interest, for which the lack of expertise and financial resources were often quoted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interestingly report from the European Food Safety Authority (EFSA) showed that in the 2016 year all Europe reference laboratories (100%) employed WGS for pathogen identification, but there were discrepancies when compared the WGS employment among other specialized institutions as National Reference Laboratories (44%) and Official laboratories (7%). The main reasons for this reduced usage by non-reference laboratories can be summarized around two variables: the limitation in the budgets of the facilities and the absence of trained staff to conduct analysis of data using bioinformatics tools (38).…”
Section: Bioinformatics: Downstream Analysismentioning
confidence: 99%
“…These fragments are later assembled into a draft or complete genome that can be used for further analysis, including gene prediction and annotation (e.g., identification of genes in the genome), comparative genomics (e.g., identification of genome variability, including single nucleotide, allelic variants and differences in gene content) and evolutionary analysis (e.g., generation of trees to depict the evolution of an organism) (Ronholm et al, 2016). A survey conducted by EFSA in 2016 showed that 17 out of 30 European countries already had capacity to perform WGS of foodborne pathogens and 22% of interviewed laboratories had ongoing routine activities involving WGS (European Food Safety Authority [EFSA], 2018). In the United States, the National Antimicrobial Resistance Monitoring System (NARMS) is performing routine WGS analysis of Salmonella and Campylobacter , in addition to some sequencing of resistant strains of Escherichia coli and Enterococcus collected from food-producing animals, retail meats and humans (Food and Drug Administration, 2018).…”
Section: Introductionmentioning
confidence: 99%